THE REVISED CONSORT STATEMENT FOR REPORTING RANDOMIZED TRIALS: EXPLANATION AND ELABORATION (2001) (ENDING) - Douglas G. Altman; Kenneth F. Schulz; David Moher; Matthias Egger; Frank Davidoff; Diana Elbourne; Peter C. Gtzsche; Thomas Lang (Столичная издательская компания, 2016)
Со списком литературы можно ознакомиться на сайте http://www.consort-statement.org